2013
DOI: 10.1107/s0021889812047085
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure phase transitions and equations of state in NiSi. III. A new high-pressure phase of NiSi

Abstract: A new high-pressure phase of NiSi has been synthesized in a multi-anvil press by quenching samples to room temperature from 1223-1310 K at 17.5 GPa and then recovering them to atmospheric pressure. The crystal structure of this recovered material has been determined from X-ray powder diffraction data; the resulting fractional coordinates are in good agreement with those obtained from an ab initio computer simulation. The structure, in which each atom is sixfold coordinated by atoms of the other kind, is orthor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 48 publications
6
33
1
Order By: Relevance
“…The sequence of stable NiSi structures originally proposed was as follows: MnP → P4/nmm (or the CuTi phase) → Pbma-I → Pnma-III (FeB) → CsCl, with transitions occurring at 23, 61, 168 and 247 GPa, respectively . Following this work, Wood et al (2013) found a new stable phase of NiSi in experiments carried out in a MAP. This new phase of NiSi, with Pmmn symmetry (an orthorhombic distortion of the tetragonal CuTi structure), had not originally been considered by Vočadlo et al (2012), but further ab initio calculations revealed that this Pmmn phase was indeed more stable than either of the P4/nmm, Pbma-I or Pnma-III (FeB) phases, resulting in a much simpler phase diagram at 0 K. The new phase stability sequence in NiSi, therefore, became MnP → Pmmn → CsCl, with transitions occurring at 21 and 264 GPa (Wood et al 2013).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The sequence of stable NiSi structures originally proposed was as follows: MnP → P4/nmm (or the CuTi phase) → Pbma-I → Pnma-III (FeB) → CsCl, with transitions occurring at 23, 61, 168 and 247 GPa, respectively . Following this work, Wood et al (2013) found a new stable phase of NiSi in experiments carried out in a MAP. This new phase of NiSi, with Pmmn symmetry (an orthorhombic distortion of the tetragonal CuTi structure), had not originally been considered by Vočadlo et al (2012), but further ab initio calculations revealed that this Pmmn phase was indeed more stable than either of the P4/nmm, Pbma-I or Pnma-III (FeB) phases, resulting in a much simpler phase diagram at 0 K. The new phase stability sequence in NiSi, therefore, became MnP → Pmmn → CsCl, with transitions occurring at 21 and 264 GPa (Wood et al 2013).…”
mentioning
confidence: 65%
“…Following this work, Wood et al (2013) found a new stable phase of NiSi in experiments carried out in a MAP. This new phase of NiSi, with Pmmn symmetry (an orthorhombic distortion of the tetragonal CuTi structure), had not originally been considered by Vočadlo et al (2012), but further ab initio calculations revealed that this Pmmn phase was indeed more stable than either of the P4/nmm, Pbma-I or Pnma-III (FeB) phases, resulting in a much simpler phase diagram at 0 K. The new phase stability sequence in NiSi, therefore, became MnP → Pmmn → CsCl, with transitions occurring at 21 and 264 GPa (Wood et al 2013). More recent static computer simulations by Gavryushkin et al (2015) confirmed the stability of the Pmmn phase but also suggested that a tetragonally distorted (a/c ~ 0.8) CsCltype structure formed above 213 GPa, becoming fully cubic above 522 GPa.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Up to 1700 K the assemblage consists of B20-NiSi plus the orthorhombic Pmmn 289 phase ( Fig. 6a and 7b; Wood et al, 2013) which are known to share a broad two-phase region. The 290…”
Section: Melt Detection 223mentioning
confidence: 99%
“…Both studies also reported equations of state (EoS) for these 49 structures as well as for the room pressure phase, at 0 K (for the ab initio study), and 300 K (for the 50 LH-DAC study). A third installment (Wood et al, 2013) reported the discovery of another high-51 pressure phase, with space group Pmmn, in multi-anvil press (MAP) experiments together with ab 52 initio simulations of this new structure, including a 0 K EoS. The present study, in which the 53 melting curve of NiSi is reported, forms a further part of this ongoing effort; it is accompanied by 54 Dobson et al (submitted) in which the sub-solidus phase relations of NiSi are described using off-55 line and in situ MAP experiments, in combination with the in situ LH-DAC experiments described 56…”
Section: Introductionmentioning
confidence: 99%